Národní korpusy a polsko-česká/ česko-polská překladová lexikografie - Charciarek, Andrzej (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2015)
The article describes the role which national corpora can and should play in creating the great Polish-Czech/ Czech-Polish dictionary. The article analyses functions of the language corpora in preparing single and multi-word dictionary entries in an e-dictionary. Concrete examples have been used for the purposes of the detailed analysis of polysemy and homonymy in the process of creating dictionary entries. Also, the methodology of monolingual lexicography (e.g. identifiers and definitions) is presented in the description of dictionary entries (words or phrasemes) in the dictionary. Particular focus is put on creating dictionary entry structure and using the national corpora. Some concrete examples have been used to illustrate selectivity and incompleteness in the description of lexical unit meanings found in dictionaries not based on the texts from the language corpora. The article emphasises the significance of language corpora in creating entries as they are a useful source of frequency data in creating dictionary entries. The article is based on the corpus data from the National Corpus of Polish (NKJP) and the Czech National Corpus (ČNK).
Keywords: lexicography; translation dictionary; corpus linguistics; Polish language; Czech language